EVALUATION OF PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF GLUTEN-FREE WHITE BREAD WITH VARIATIONS IN THE PROPORTIONS OF MOCAF FLOUR AND MUNG BEAN FLOUR - Alfia Nur Rofida; Kejora Handarini; Bambang Sigit Sucahyo; Dewi Mariyanah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Bread is a processed food product that is widely consumed as a substitute for rice or as a snack because of its popular taste in Indonesia. MOCAF (Modified Cassava Flour) is fermented cassava flour that has a smooth texture, white color, neutral aroma, and is gluten-free, while mung bean flour is a source of high vegetable protein (±22.9%) and is rich in vitamins and minerals so it has the potential to increase the nutritional value of processed food products. This study aims to determine the effect of the proportion of MOCAF flour and mung bean flour and to determine the best treatment on the physicochemical and organoleptic properties of gluten-free white bread. The study was conducted using a laboratory experimental method with a one-factor Completely Randomized Design (CRD) consisting of four treatments, namely P1 (100%:0%), P2 (85%:15%), P3 (80%:20%), and P4 (75%:25%), each with three replications. The parameters analyzed included swelling power as a physical property, water content , crude fiber, and protein as chemical properties, and color, taste, aroma, and texture as organoleptic properties. The results showed that treatment P2 produced the best characteristics with a protein content of 13.306%, fiber 2.436%, water content 37.546%, swelling power 1.726%, and an average organoleptic value of 3.2 (neutral). These results indicate that MOCAF flour and mung bean flour have the potential as alternative raw materials for gluten-free white bread based on local food.